Differences in the Synovial Fluid Proteome of Septic and Aseptic Implant Failure - Andrea Sowislok; André Busch; Farnusch Kaschani; Markus Kaiser; Marcus Jäger (MDPI AG, 2024)
Implant loosening is a severe complication after total joint replacement. Here, differential diagnosis between septic and aseptic cases is crucial for further surgical treatment, but low-grade periprosthetic joint infections (PJIs) in particular remain a challenge. In this study, we analyzed the synovial fluid proteome of 21 patients undergoing revision surgery for septic (eight cases) or aseptic (thirteen cases) implant failure using LC-MS/MS to identify potential new biomarkers as future diagnostic tools. Staphylococci were found in four cases, Streptococci in two cases, Serratia marcescens and Cutibacterium acnes in one case. Proteomic analysis of the synovial fluid resulted in the identification of 515 different proteins based on at least two peptides. A statistical comparison revealed 37 differentially abundant proteins (p < 0.05), of which 17 proteins (46%) showed a higher abundance in the septic group. The proteins with the highest fold change included the known marker proteins c-reactive protein (7.57-fold) and the calprotectin components protein S100-A8 (4.41-fold) and protein S100-A9 (3.1-fold). However, the protein with the highest fold change was leucine-rich alpha-2-glycoprotein 1 (LRG1) (9.07-fold), a currently discussed new biomarker for inflammatory diseases. Elevated LRG1 levels could facilitate the diagnosis of PJI in the future, but their significance needs to be further investigated.